Life estimation and investigation of dielectric strength of multistressed high‐voltage epoxy micro and nanocomposites. (1st November 2016) - Amin, Muhammad; Khattak, Abraiz; Ali, Muhammad
Abstract : Epoxy/silica micro and nanocomposites are prepared and subjected to multiple accelerated stresses along with neat epoxy for 9000 h in a specially fabricated chamber. Leakage current measurements were recorded after each weather cycle. Dielectric strength was also evaluated according to ASTM‐D149 after each 1000 h ageing. In the course of ageing time, neat epoxy was found with high dielectric loss and random rise in leakage current. In the case of both micro and nanocomposites, these properties indicated improvements over neat epoxy. By applying regression technique over leakage current measurements, relatively longer service lives of epoxy composites were estimated.